(untitled) (Lex Mercatoria, 2025)
This study discusses the relevance of Islamic Sharia within the context of Indonesia’s constitutional system by employing a descriptive qualitative approach through library research. The purpose of this study is to provide an in-depth understanding of the relationship between the principles of Islamic Sharia and the practice of state governance in Indonesia from a practical perspective. The historical approach is used to trace the process of the introduction and development of Islamic Sharia in the Nusantara region and its influence on the formation of Indonesia’s legal and governmental systems. Meanwhile, the normative-philosophical approach is utilized to analyze the fundamental values and principles of Islamic Sharia and their relevance to the constitutional system based on Pancasila and the 1945 Constitution of the Republic of Indonesia. The findings indicate that Islamic Sharia has had a significant influence on the formation of Indonesia’s legal, social, political, and cultural systems from the pre-colonial period to the contemporary era. In the modern context, the implementation of Islamic Sharia in Indonesia is not formalistic but rather substantive and practical. Islamic values are integrated into the state governance system through public policies, legal regulations, and political ethics that emphasize the principles of justice, trustworthiness, and social welfare. Accordingly, the existence of Islamic Sharia in Indonesia serves as a moral and ethical foundation that strengthens the constitutional system in realizing a just, civilized, and socially equitable national life. Keywords: Islamic Sharia, Indonesian constitutional system, Islamic law, Pancasila, praxis